A solution for the over-the-horizon-radar simulator - Džolić, Bojan; Veinović, Mladen; Orlić, Vladimir; Lekić, Nikola; Grbić, Nemanja (Vojnotehnički glasnik / Military Technical Courier, 2020)
Introduction/purpose: The OTHR simulator presented in this paper is developed and used in practice, with the aim of emulating radar signal environment, but also optimizing the radar parameters in real applications such as: radiated power, antenna array gain, path loss, radar cross section, external interference, and noises. Methods: In this paper, the methodology of mathematical modeling is used as well as simulations . Results: Based on the performed analysis, the output data from the OTHR simulator is presented and discussed. Conclusion: The usage of the presented OTHR simulator makes assessing the reliability of a potential radar at predetermined locations automated, controllable and efficient, with results closely matching radar behavior in real operation.